Distribution of the flux of fotons in the difraction pattern from one and two parallel slits - Безуглый, А.В.; Петченко, А.М. (Radiotekhnika, 2017)
The paper proposes a quantum mechanical model of the phenomenon of light diffraction on one and two slits in an infinitely thin metal screen. Based on the assumption that the photons passing through the slits interact with the electrons of the matter through elastic collisions, the resulting distribution of light intensity in the diffraction pattern for the cases of diffraction of particles in one and two cracks was obtained.